The Effect of Leaf-Eating Pest Infestation on Pakcoy (Brassica rapa L.) Cultivation Treated with Papaya Leaf Extract - Nurfitriah Nurfitriah; Akhmad Gazali; Antar Sofyan (Formosa Journal of Science and Technology, 2023)
Pakchoi (Brassica rapa L.) has experienced a decline in productivity due to plant pests. The objective of this research was to determine the effect of papaya leaf extract and the optimal concentration that can control pest infestation. This study utilized a Randomized Block Design (RBD) consisting of 4 treatments with 5 replications, with the tested concentrations being: P0 = control, P1 = 200 ml L-1, P2 = 400 ml L-1, P3 = 600 ml L-1. The research results indicated that papaya leaf extract significantly influenced pest attacks, with the best concentration being 600 ml L-1, resulting in a pest attack intensity of 18.75%.